Citizen participation in accountability to health management in Cali, Colombia (Colombia Medica, 2009)
Background: In Latin American for improving health sector performance and for decreasing corruption process, a social control initiatives like accountability process are been realized by social actors involved in health sector. Objectives: To describe and to analyze accountability to health management process with the involvement of health services consumers. Methodology: A pilot control social experience was developed in Cali with community participation in an accountability experience. Three public accountability experiences were developed. A methodology proposal was design to achieve community participation in accountability process. Results: 745 persons, indirectly, and 54 community leaders of Consumer Association of health local services of Cali, directly, were wrapped up. They had technical support in two out of the three accountability meetings carried out. In each stage was identified technical and methodological weakness in the accountability process. Conclusions: Despite of an understanding of the accountability process in health was improved, the experience showed some obstacles such as: difficulties in the access of information, low community leadership in social control issue and resistance of public health workforce to see their performance in health sector as a matter to be account.